“Everything is Research” – a brief reflection on how wizards and Barbie dolls are developing my understanding of binaries in my different contexts - Kate Meredith (Murmurations)
This writing reflects on how binaries and labels can present themselves for exploration and irreverence in all contexts, from systemic practice in a multidisciplinary team to enjoying theatre, TV and music with family. When we see "everything is research" as practitioner-researchers, we can use any opportunity to consider our positions, both privately and in dialogue with others, and challenge ourselves to work towards ethical congruence in our many contexts.